Occupational safety and health performance in the Pakistani construction industry: stakeholders' perspective. Issue 3 (2nd July 2016) - Zahoor, Hafiz; Chan, Albert P.C.; Masood, Rehan; Choudhry, Rafiq M.; Javed, Arshad A.; Utama, Wahyudi P.
Abstract : Lack of compliance with Occupational Safety and Health (OSH) has resulted in a relatively higher construction accident rate in developing countries such as Pakistan. This study attempts to unveil the aspects of OSH that are ignored and discern the differences in the perceptions of key construction stakeholders. Data collected from 195 respondents were analysed using Cronbach's coefficient alpha, Shapiro‒Wilk and Kruskal‒Wallis tests. The results indicate that OSH training is the most neglected factor, followed by non-inclusion of safety in contract documents and workers' non-involvement. Stakeholders have dissimilar perception about three OSH factors, including management commitment to OSH, safety rules/procedures and policies, and OSH training. Regulatory authority is suggested to launch OSH awareness campaigns, announce safety incentives, institutionalize the OSH certification system, and incorporate safety credit points in contractors' registration process. Though this study pertains to Pakistan, the methodology and the recommendations can be generalized for other developing countries with a similar work environment.